Surveillance and control of cassava diseases in Africa - International meeting results in Pan-African cassava disease network - (:unkn) unknown (My University, 2016)
Cassava is the most important vegetatively propagated food staple crop in Africa. Even if its vegetative propagation through stem cuttings has many advantages, it also represents its Achilles heel. Pathogens are passed from one generation to the next and can easily accumulate, threatening cassava production. Two viral diseases are currently considered to be the greatest global threat to cassava production in Africa. Faced with the gravity of this situation, 43 scientists from African national and regional institutions and international agricultural research centres met in Saint-Pierre, La Réunion Island from 10 to 13 June 2014, to contribute to the surveillance and control of cassava diseases and pests that threaten the food security and livelihoods of millions Africans. The main action was to consolidate and develop a global alliance against cassava diseases in Africa and a strategic action plan with several international initiatives for the coming years. Firstly, the establishment of a Pan-African Cassava Surveillance Network (PACSUN) with an interactive website and an International Cassava Transit Site (ICTS) in La Réunion. Secondly, the development of diagnostic technologies to better identifying viruses, bacteria and vectors, and a comprehensive educational and training plan to support all these activities. (Texte intégral)
Keywords: African Research